University economics - Alchian, Armen A. (Belmont, 1964)
Man wants more than there is any prospect of obtaining. As soon as we have more of this, we want still more of it and more of that... and that. To say that we always want more is to say that man lives, even in the most affluent societies, in a state of scarcity. The response to scarcity - What determines how much each person produces and gets of the total? And what determines the particular mix of goods and services s/he consumes? -- constitutes the area of economic study. Economics studies the competitive and cooperative behavior of people in resolving conflicts of interest that arise because wants exceed what is available.
Keywords: Economics